GENDER DISPARITY ON THE GLOBAL STAGE: THE ENDURING IMPACT OF MNCS - Smith, Marcus Reynolds; Srivastava, Priya Singhania (American Journal of Legal Practice (AJLP), 2023)
This article explores how multinational corporations (MNCs) discriminate against women in their workforce. MNCs are a crucial source of employment opportunities for women, particularly in the consumer goods and service sectors. Despite this, MNCs often pay women less than men, subject them to poor working conditions, and terminate their employment without notice in times of economic downturn. The article presents case studies of Colgate-Palmolive and Ford Motor Company to support these claims. Additionally, the article highlights the lack of accountability held by MNCs for violating human and labor rights in both their home state and host state. The legal regime fails to provide a framework to address gender discrimination, and international law does not hold MNCs accountable. The article argues for the need to establish an international legal standard to protect women's rights in MNCs, which must be versatile enough to address various types of discrimination against women. This non-empirical paper draws from treaties, declarations, academic journals, books, and website materials relevant to women's rights.